Preface Proceedings ICBE-HOU 2022 - Dimitras, Augustinos; Peppas, George; Vilou, Aimilia (International Conference on Business and Economics - Hellenic Open University, 2023)
This Conference Proceedings’ volume includes 15 articles selected among 75 papers submitted to the Eighth ICBE - HOU, which was successfully held on June 17-18, 2022. We followed a double-blind peer review process for the submitted papers, in which reviewers were either members of the Scientific Committee or external ones. With this second volume, the Conference maintains its commitment to encourage and promote high-quality works in the field of Business Administration by providing Open Access publishing.